P712 Establishing pharmacokinetic equivalence between adalimumab and ABP 501 in the presence of anti-drug antibodies using population PK modelling. (16th January 2018) - Doshi, S; Krishnan, E; Wang, H; Zhang, N; Chow, V
Abstract: Background: Adalimumab (Humira ® ) and its approved biosimilar ABP 501 (AMGEVITA ® ; adalimumab) exhibit nonlinear pharmacokinetics (PK) following a single subcutaneous (SC) dose in healthy volunteers possibly due to target mediated disposition or development of anti-drug antibodies (ADAs). The presence of nonlinear PK leads to low and variable drug levels posing a challenge in assessing PK equivalence of these two agents. To address this we used a population PK modelling approach to assess PK equivalence. Methods: A one-compartment linear PK model with first-order absorption was selected to characterise the ABP 501 and adalimumab PK in healthy subjects. The model was parameterised in terms of apparent systemic clearance and apparent central volume of distribution for subjects with or without ADAs. Body weight, albumin and ADA status were evaluated for their potential impact on adalimumab or ABP 501 PK. For subjects who developed ADAs, the model evaluated the inclusion of additional antibody mitigated clearance mechanisms using Michaelis–Menten (MM) type of saturable clearance or time-dependent changes in linear clearance. The effect of treatment on PK parameters was evaluated by comparisons of the empirical Bayes' estimates of the individual PK model parameters. Results: In healthy subjects without ADAs, the ABP 501 and adalimumab PK after SC administration was linear and adequately described by a one-compartment model with first-order absorption and linear clearance from the central compartment. Inclusion of an additive time dependent linear clearance for subjects with ADAs was superior to a model incorporating an additive MM saturable clearance for subjects with ADAs. Graphical and statistical comparisons of empirical Bayes' estimates by treatment demonstrated no difference in any PK model parameters by treatment. The population and inter-individual variability estimates of clearance and volume were 0.399 (33.6%) l/day and 8.94 (23.5%) l, for a 72.7 kg subject (median body weight). The time to onset and magnitude of the additive ADA-related linear clearance was 33.7 (54.4%) days and 1.15 (52.6%) l/day. Diagnostic plots demonstrated good concordance between observed and population or individual predicted concentrations without any bias. Visual predictive checks demonstrated the model described well the variable PK following a single dose of ABP 501 or adalimumab. The model described the PK of each individual well and was used to estimate accurately each individual's area under the concentration curve (time 0 to infinity) for all 203 subjects who completed the study. Conclusions: The present population PK modelling confirms PK similarity of ABP 501 to adalimumab.